"Someone Is Watching Me While I Write": Monolingual Ideologies and Multilingual Writers Behind the Scenes of L2 Writing Tutorials. Issue 1 (4th September 2021) - Elabdali, Rima
Abstract: In the present study, I draw on Canagarajah's (2019) negotiated‐literacy orientation and the systemic functional linguistic (SFL) approach to discourse analysis (Eggins & Slade, 1997) to demonstrate the varying degrees to which Fatima and Chow, two multilingual doctoral students, were able to question and negotiate normative literacy practices during L2 writing tutorials and how such negotiations may be impacted by the language ideologies internalized by the writers and/or their tutor. The main sources of evidence were interviews with the two doctoral students and excerpts from audio‐recorded writing tutorials, complemented with stimulated‐recall data contrasting tutor and writer interpretations of the same recorded literacy events. The results suggest that the variable degree to which the two multilingual writers are cognizant and resistant of monolingual ideologies impacted their orientation to negotiate literacy in the tutorials. In addition, some of the tutor's interactional practices were seen to restrict the space for meaning negotiations and hamper the potential to reconcile the diverse literacy dispositions of the tutor and the two multilingual writers. By grounding aspects of negotiated literacy in specific discourse‐semantic moves, the study puts forth implications for a more critical tutoring pedagogy. Abstract :